Novel multi-target ligands of dopamine and serotonin receptors for the treatment of schizophrenia based on indazole and piperazine scaffolds-synthesis, biological activity, and structural evaluation - Piotr Stępnicki; Olga Wronikowska-Denysiuk; Agata Zięba; Katarzyna M. Targowska-Duda; Agata Bartyzel; Martyna Z. Wróbel; Tomasz M. Wróbel; Klaudia Szałaj; Andrzej Chodkowski; Karolina Mirecka; Barbara Budzyńska; Emilia Fornal; et al. (Taylor & Francis Group, 2023)
Schizophrenia is a chronic mental disorder that is not satisfactorily treated with available antipsychotics. The presented study focuses on the search for new antipsychotics by optimising the compound D2AAK3, a multi-target ligand of G-protein-coupled receptors (GPCRs), in particular D2, 5-HT1A, and 5-HT2A receptors. Such receptor profile may be beneficial for the treatment of schizophrenia. Compounds 1-16 were designed, synthesised, and subjected to further evaluation. Their affinities for the above-mentioned receptors were assessed in radioligand binding assays and efficacy towards them in functional assays. Compounds 1 and 10, selected based on their receptor profile, were subjected to in vivo tests to evaluate their antipsychotic activity, and effect on memory and anxiety processes. Molecular modelling was performed to investigate the interactions of the studied compounds with D2, 5-HT1A, and 5-HT2A receptors on the molecular level. Finally, X-ray study was conducted for compound 1, which revealed its stable conformation in the solid state.